Implementasi Kebijakan Turisme Berkesinambungan di Kabupaten Banyuwangi Periode 2010-2021 dan Periode 2021-2024 - Syah, Kansul Fikri; Adi, Isbandi Rukminto (IAI Nasional Laa Roiba Bogor, 2024)
Banyuwangi Regency is considered successful in implementing sustainable tourism policies, as evidenced by the many awards and the designation of Banyuwangi as part of the global geopark chain known as Ijen UNESCO Global Geopark. This cannot be separated from natural potential, rich flora and fauna, cultural diversity and geographical location as well as the commitment of local governments in implementing these policies. Then what becomes interesting is when there is a change of government, whether the implementation of sustainable tourism policies continues or whether there are changes such as differences and similarities between the two periods. The research method uses a descriptive qualitative approach, while data collection is through related documents, non-partisan observation, and in-depth interviews with 16 informants. The results of the research are that there are differences in the implementation of sustainable tourism policies, in the period 2010 to 2021 prioritizing development through tourism instruments for local economic development and creating social welfare, and in the period 2021 to 2024 using instruments to strengthen the local economy with micro and small business policies and medium to generate economic capital in the community during and after the Covid-19 pandemic, but without abandoning the implementation of sustainable tourism policies.